Water vapour sorption characteristics and surface chemical composition of thermally modified spruce (Picea abies karst). (2nd July 2016) - Källbom, S.; Rautkari, L.; Wålinder, M.; Johansson, L.-S.; Campbell, J. M.; Segerholm, K.; Jones, D.; Laine, K.
Abstract : The objective of this work was to study the hygroscopicity and surface chemical composition of thermally modified (TM) spruce. An effort was also made to study if those features were influenced by a previous exposure to a significant increase in relative humidity (RH). TM and unmodified Norway spruce ( Picea abies Karst) samples, both in solid and ground form, were prepared. Water vapour sorption characteristics of the ground samples were obtained by measuring sorption isotherms using a dynamic vapour sorption (DVS). The surface chemical composition of the solid samples, both acetone extracted and non-extracted, were analysed using X-ray photoelectron spectroscopy (XPS). The DVS analysis indicated that the TM wood exposed to the 75% RH revealed a decrease in isotherm hysteresis. The XPS analysis indicated a decrease of acetone extractable or volatile organic components and a relative increase of non-extractable components for the samples exposed to the increased RH condition.